Successful Management of Nosocomial Ventriculitis and Meningitis Caused by Extensively Drug-Resistant Acinetobacter baumannii in Austria. Issue 3 (2013) - Hoenigl, M; Drescher, M; Feierl, G; Valentin, T; Zarfel, G; Seeber, K; Krause, R; Grisold, AJ
Abstract : Nosocomial infections caused by the Gram-negative coccobacillus Acinetobacter baumannii have substantially increased over recent years. Because Acinetobacter is a genus with a tendency to quickly develop resistance to multiple antimicrobial agents, therapy is often complicated, requiring the return to previously used drugs. The authors report a case of meningitis due to extensively drug-resistant A baumannii in an Austrian patient who had undergone neurosurgery in northern Italy. The case illustrates the limits of therapeutic options in central nervous system infections caused by extensively drug-resistant pathogens.